2021
DOI: 10.1044/2021_jslhr-21-00151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capsaicin Atomization–Induced Cough on Sputum Excretion in Tracheotomized Patients After Hemorrhagic Stroke: A Randomized Controlled Trial

Abstract: Background Timely and effective removal of respiratory secretions is of great significance for tracheotomized patients. The purpose of this study is to investigate the effectiveness of capsaicin nebulization to stimulate cough to promote early clearance of respiratory secretions in tracheotomized patients after hemorrhagic stroke. Method This study implemented a randomized controlled design. Sixty-three patients who were tracheotomized following a hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…A possible hypothesis is that capsaicin should aid the clearance of the laryngopharynx and lower airways. In addition, a repeated trigger of the cough reflex might induce a central recovery of the cough reflex contributing to dysphagia rehabilitation as demonstrated in a recent case report in subjects affected by stroke [29] and in tracheostomized subjects affected by hemorrhagic stroke [30]. Another study conducted by Cui et al demonstrated an improvement in the swallowing function by combining ice and capsaicin stimulation in subjects with dysphagia after stroke [31].…”
Section: Discussionmentioning
confidence: 96%
“…A possible hypothesis is that capsaicin should aid the clearance of the laryngopharynx and lower airways. In addition, a repeated trigger of the cough reflex might induce a central recovery of the cough reflex contributing to dysphagia rehabilitation as demonstrated in a recent case report in subjects affected by stroke [29] and in tracheostomized subjects affected by hemorrhagic stroke [30]. Another study conducted by Cui et al demonstrated an improvement in the swallowing function by combining ice and capsaicin stimulation in subjects with dysphagia after stroke [31].…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, inhalation therapy with nebulized capsaicin for the purpose of minimizing aspiration and pneumonia risk in alert and cooperative patients post stroke has not been describe in the literature to date [ 47 ]. We are aware of one recently published randomized controlled trial by Wu et al [ 48 ], in which tracheotomized patients post hemorrhagic stroke with moderate to severe impairment of consciousness received one week of four times daily capsaicin nebulization via a tracheostomy mask. This trial reported some positive preliminary findings, with higher sputum output, fewer required suctioning passes and lower clinical pulmonary infection scores in the group that received capsaicin nebulization [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3] However, some patients may experience difficulties with tube removal, and prolonged tracheostomy tube placement can lead to other complications, significantly impacting the patient's rehabilitation process. [4] This requires active intervention.…”
Section: Introductionmentioning
confidence: 99%